Advanced Science and Technology Letters 2013
DOI: 10.14257/astl.2013.39.24
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Affective Color Transfer Using Feature Based Facial Expression Recognition

Abstract: Emotion recognition is one of the most important factors in emotional ICT. In this paper, we suggest the system of emotion affective color transfer. To recognize human emotion, we use feature based facial expression recognition. Suggested system can be affected Image contents according to individual emotion. To emotionally transfer image contents, we analyze color, shape and stroke information. Emotion affective system can be used various multimedia contents such as music, movie and game.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The automated recognition of emotions [1][2][3][4][5][6] through computational analysis is a challenging task in the field of computer vision. Facial expressions [7][8][9] are fundamental in this sense since they are one of the main signs of humanity's emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The automated recognition of emotions [1][2][3][4][5][6] through computational analysis is a challenging task in the field of computer vision. Facial expressions [7][8][9] are fundamental in this sense since they are one of the main signs of humanity's emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Several works [2][3][4][6][7][8]10,11,14,15,31 have been developed by the scientific community to automatically recognize facial expressions. Some methods are based on the recognition of emotions, whereas others are based on the recognition of facial muscle actions or facial action units.…”
Section: Introductionmentioning
confidence: 99%
“…We considered the first human as the experiment subject and the second human as the control subject. Based on the human-human study, we found the following major task situations/contexts/events and the corresponding affects, as given in Table 2 [45][46][47][48]. Table 2 shows the major events that occurred during the human-human collaboration and the ways the humans, especially the first humans, expressed the situations/events through affective expressions.…”
Section: Inspiration From a Human-human Collaborative Task: The Biomi...mentioning
confidence: 99%
“…To name a few exceptional studies, Hakim, Marsland, and Guesgen [35] used data on human faces, in which experts labelled the revealed emotion on them as training data for video classification. In addition, Ryoo and Chang [36] associated the color features of videos with the expressed emotion on human faces. However, relatively little attention has been paid to the facial emotions on human faces in affective content analysis of video, and the emotional differences according to the attributes of the video have been particularly understudied.…”
Section: Related Work a Affective Content Analysis Of Videomentioning
confidence: 99%